Pedagogical and Personal Experiences Motivating Indigenous Students to Pursue Medical Studies - Chichekian, Tanya; Bragoli-Barzan, Léa; Rahimi, Sonia (Frontiers in Education, 2022)
When it comes to accessibility to healthcare and medical education, inequalities prevail within ethnically diverse populations, especially among Indigenous Peoples. The main objective of this qualitative study was to explore how Indigenous female medical students' motivations played a role in their pursuit of a medical career. We use the Self-Determination theory to frame this study and conduct individual open-ended interviews with four female Indigenous students’ regarding their motivational sources for applying to medical school. We provide an illustrative scenario for each identified motivational source through a thematic analysis. Results revealed two main sources of motivations: (1) pedagogical experiences (i.e., contextual factors at school, academic interests, and opportunities) and (2) personal experiences (i.e., family support and influence, and future career prospects). Indigenous students’ personal experiences were more prevalent and described autonomous forms of motivations, whereas sources of motivation that were pedagogically oriented reflected more controlled forms of motivations. Different types of motivations can be useful, but not sufficient for the tipping point when the time comes for medical school applications. Learning about specialized Indigenous streams for admissions played the most influential role in students’ decision-making to pursue medical studies. Promoting the visibility of the Indigenous stream coupled with the identification of different forms of motivation could be informative when outlining evidence-based recommendations with the aim of improving inequalities within the health professions.